Determination of mass transfer parameters and swelling factor of CO2-oil systems at high pressures - Rezk, M.G. (Elsevier Ltd, 2018)
The rate of CO2 dissolution in crude oils is primarily controlled by mass transfer between CO2 and oil phases. In particular, mass transfer of CO2 component across the CO2-oil interface and the molecular diffusion of CO2 inside the oil phase control the rate of CO2 dissolution in the oil. The values of interface mass transfer coefficient (k) and diffusion coefficient (D) are needed to estimate the mass transfer rate by molecular diffusion and to determine the CO2 dissolution rate in a crude oil. When CO2 is dissolved in a crude oil, the oil volume usually increases (oil swelling) that should be considered. This paper aims to accurately estimate and quantify the mass transfer parameters of CO2 in crude oils (k and D coefficients) and also the oil swelling percentage by analyzing the data of the pressure decay experiment. A mathematical model has been developed when a numerical method is used to solve the governing equations with a moving boundary condition. The model is used to analyze the data of pressure decay experiments of a heavy and also a light crude oil-CO2 system. The model has estimated the k and D coefficients of CO2 in crude oils using an optimization procedure, and also has predicted the dynamic process of oil swelling due to CO2 dissolution. The mass transfer process is discussed and the estimated mass transfer parameters (k and D) are compared with some data from the literature. The results show that the k and D values and also the oil swelling percentage for the light oil-CO2 system are larger than those for the heavy oil-CO2 system. This study gives an insight into the mass transfer process between CO2 and oil phases that can be used to describe the mass transfer process in any gas-liquid system. Â© 2018 Elsevier Ltd